Urgensi Ethical Leadership dalam Mencegah Fraud dan Kecurangan di Organisasi: Analisis Deskriptif Literatur - Hani Humaeriyah; Asyam Faris Khoirul; Hammam Rizky Ibrahim; Salsabila Fauzia Khaerani; Feby Rahmania Triana; Shinta Setiyani; Alda Audia Ambardi; Idzni Fatasya Zulqisthi; Iqbal Alamsyah (Indo Publishing, 2026)
Fraud remains a persistent threat to organizational stability that has proven insufficient to be addressed solely through technical controls, necessitating a behavioral approach. This study aims to analyze the urgency of ethical leadership in preventing fraud through a descriptive literature analysis. The research method used is qualitative with a library research approach, reviewing relevant journal articles published between 2020 and 2025. The results indicate that the urgency of ethical leadership lies in two primary mechanisms: (1) Breaking the chain of